Order Estimates for the Best Approximations and Approximations by Fourier Sums in the Classes of Convolutions of Periodic Functions of Low Smoothness in the Uniform Metric - Serdyuk, A. S.; Stepanyuk, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We obtain the exact-order estimates for the best uniform approximations and uniform approximations by Fourier sums in the classes of convolutions of periodic functions from the unit balls of the spaces L_p, 1 ≤ p < ∞, with generating kernel Ψ_β for which the absolute values of its Fourier coefficients ψ(k) are such that ∑_k = 1^∞ ψ_p ′(k)k^p ′ − 2